Time evolution of microbiological quality and content of volatile compounds in chicken fillets packed using various techniques and stored under different conditions - M. Chmiel; M. Roszko; E. Hać-Szymańczuk; L. Adamczak; T. Florowski; D. Pietrzak; A. Cegiełka; M. Bryła (Poultry Science, 2020)
The aim of this study was to evaluate dependence of microbiological quality of chicken fillets and profile of volatile compounds in their packages on the applied packaging technique and storage conditions. Samples packaged in either normal atmosphere (AP, air packaging, PVC overwrap), in modified atmosphere with high oxygen content (Hi-O2-MAP), or in vacuum (VP) were stored in a cold room or exposed in a display case for 8 days. Quality of the meat was determined on day 1, 3, 6, 7, and 8 of the storage or exposition time. The microbiological quality of chicken fillets was assessed by determining the number of mesophilic aerobic bacteria, lactic acid bacteria, Pseudomonas spp. bacteria, and Enterobacteriaceae family bacteria. The profile of volatile compounds in the packaging of chicken fillets was also determined. At the beginning of the storage, bacteria of all major groups were growing at similar rates regardless of the used packaging technique. However, at the end of the period, the growth dynamic was diversified. The profile of the volatile compounds did not depend on the storage or exposition time regardless of the storage conditions and/or the packaging technique. The results of this study indicate that there is a potential to gain understanding of spoilage of packed chicken meat through the analysis of volatile compounds in association with microbiological analysis. However, future research should be based on standardized material with similar bacterial load.